(untitled) (Research, Society and Development, 2020)
This work aims to identify the care related to instrumental actions provided to people with chronic venous ulcers relevant to the management of care. This is a methodological study developed with 30 participants, with the virtual environment as the field of investigation. The collection took place from august to december 2018, through the form of identification data of the research participants and the script for identifying care for people with chronic venous ulcers. The results showed that the instrumental actions described prioritize direct care, integrating the categories: anamnesis, exams, physical examination, care for the injury and nutritional aspects. In view of the above, it is concluded that the management of care must go through planning of actions in relation to the care identified as relevant, delegation of actions when this is not the responsibility of the nursing professional, considering that assistance to patients affected by chronic venous ulcers requires actions multidisciplinary teams, as well as foresee and provide necessary resources for assistance.